Comparative Transport Studies of '1212' Superconductors - Albert Gapud; Judy Wu; Shaolin Yan; Yi-Yuan Xie; Byeongwon Kang; Michael Siega; Don Overmyer (Science Diliman, 1999)
HgBa2CaCu2O6+δ (Hg -1212) thin films were fabricated by exchanging the T1 cations in TlBa2CaCu2O7-δ (Tl-1212) thin films with Hg cations, causing a 30-K increase in Tc. To determine how this exchange effects such a Tc increase, the irreversibility lines, temperature dependence of critical current density, and temperature dependence of Hall angle ofHg-1212 and TI-1212 thin films were measured and then compared. The results strongly suggest that the Tc shift is caused by a doubling of charge carrier density.